Toward a culture of consequences : performance-based accountability systems for public services : executive summary - Stecher, Brian M. (Rand Corporation monograph series., 2010)
Performance-based accountability systems (PBASs), which link incentives to measured performance as a means of improving services to the public, have gained popularity. While PBASs can vary widely across sectors, they share three main components: goals, incentives, and measures. Research suggests that PBASs influence provider behaviors, but little is known about PBAS effectiveness at achieving their performance goals or about government and agency experiences. This document summarizes a study that examined nine PBASs in five sectors: child care, education, health care, public health emergency preparedness, and transportation. In the right circumstances, a PBAS can be an effective strategy for improving service delivery. Optimum circumstances include having a widely shared goal, unambiguous observable measures, meaningful incentives for those with control over the relevant inputs and processes, few competing interests, and adequate resources to design, implement, and operate the PBAS. However, these conditions are rarely fully realized, so it is difficult to design and implement PBASs that are uniformly effective. PBASs represent a promising policy option for improving the quality of service-delivery activities in many contexts. The evidence supports continued experimentation with and adoption of this approach in appropriate circumstances. Even so, PBAS design and its prospects for success depend on the context in which it will operate. Also, ongoing system evaluation and monitoring are integral components of a PBAS; they inform refinements that improve system functioning over time.